Schnapps of the stubble: Memory and identity in Viotá - Cundinamarca - Velásquez-Mantilla, Daniel A. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper aims to understand the meanings of sociocultural practices in the peasant production of Schnapps of the stubblein the municipality of Viotá, province of Tequendama in Cundinamarca, Colombia. It is an ethnography that is achieved through the collection of different experiences and narratives about liquor production in the region. Its practices are considered intangible cultural heritage, arising from the coexistence of knowledge built within the framework of the history of the first emancipation, civil wars and agrarian struggles, which give foundation to memory and peasant identity.